A geometric approach to the extended D'Alembert principle of Udwadia-Kalaba-Hee-Chang - Solomín, Jorge Eduardo (2005)
The extended D'Alembert Principle introduced by Udwadia, Kalaba, and Hee-Chang (1997) is analyzed in the framework developed by Vershik and Fadeev (1981) and shown to be equivalent to the general version of the Principle of virtual work presented therein.